Intention to Install Green Infrastructure Features in Private Residential Outdoor Space - Ordóñez Barona, Camilo; Conway, Tenley M.; Roman, Lara A. (Frontiers in Sustainable Cities, 2021)
Green infrastructure (GI) features in private residential outdoor space play a key role in expanding GI networks in cities and provide multiple co-benefits to people. However, little is known about residents’ intended behavior concerning GI in private spaces. Resident homeowners in Toronto (Ontario, Canada) voluntarily participated in an anonymous postal survey (n=533) containing questions related to likelihood to install additional GI features in their private outdoor space; experiences with this space, such as types of uses; and environmental concerns and knowledge. We describe the association between these factors and people’s intention to install GI in private residential outdoor space. Factors such as environmental concerns and knowledge did not influence likelihood to install GI. However, experiences with private residential outdoor space, such as nature uses of this space, level of self-maintenance of this space, and previously installed GI features, were significant influences on the likelihood to install GI. These findings have important implications for managing GI initiatives and the adoption of GI in private residential spaces, such as orienting communication materials around uses of and experiences with outdoor space, having programs that generate direct experiences with GI features, and considering environmental equity in such programs.